Java2 Enterprise Edition 1.4 (J2EE 1.4) Bible. - Adatia, Rahim; Fain, Yakov; Gordon, Jason; Henry, Ethan; Hurst, Walter; Jain, Ashish; Little, Mark; Nagarajan, Vaidyanathan; Oak, Harshad; Phillips, Lee Anne (Wiley, 2011)
Java 2 Enterprise Edition (J2EE) is the specification that all enterprise Java developers need to build multi-tier applications, and also the basis for BEA's WebLogic Application Server and IBM's WebSphere Revised to be current with the significant J2EE 1.4 update that will drive substantial developer interest Written by a top-selling team of eleven experts who provide unique and substantial business examples in a vendor-neutral format, making the information applicable to various application servers Covers patterns, J2EE application servers, frameworks, Ant, and continuous.